(3TQM GddHGH GdMGOj YTQ aj GdCUhd GdNeSIs - (3GdSjhQj, GdMdj, GdCSOj, GdebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826(3g`s ((3YHO Ydj Hf CMeO GHf eMeO GdHMQGfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Od Ydi hLhH hLhOg GaJbGQ GdeecfGJ(B... (3CeG HYO aEf Gddg JYGdi de jNdb GdYGde YHKG(B...(3cGf bO Sda efj aj SGda GdReGf Cf CcJH TjFG (B...(3hSejJg GdfGaY jhe GdeMTQ(B...s
(3BNQgG (B:s
(3GdQGHY ef GdCeQ hGdfGgj ef GVQQ GdMGUd HSHH GdCeQ hGdfgj(B... (3agPG eG JgjC dj JJejeg hcJGHJg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B282s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B470s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B616s
(3GdPQjYI HQbe(B: 129s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds